Going down the slippery slope of legitimacy lies in early‑stage ventures: the role of moral disengagement - Theoharakis, Vasilis; Voliotis, Seraphim; Pollack, Jeffrey M. (Springer, 2020)
It would seem, on the surface, logical that entrepreneurs would treat stakeholders with honesty and respect. However, this is not always the case—at times, entrepreneurs lie to stakeholders in order to take a step closer to achieving legitimacy. It is these legitimacy lies that are the focus of the current work. Overall, while we know that legitimacy lies are told, we know very little about the psychological processes at work that may make it more likely for someone to tell a legitimacy lie. Thus, we theorize about the pressure to pursue legitimacy, the situational and individual factors that affect this pursuit, as well as how this context can lead to moral disengagement and the telling of legitimacy lies. Our theorizing advances the existing literature and provides a dynamic framework by which future research can delve more deeply into the nuanced context that breeds the escalation of legitimacy lies.
Keywords: New ventures; Unethical decision-making; Legitimacy lies; Moral disengagement